Therapeutic Effect of Acupotomy at Sanheyang for Cartilage Collagen Damage in Moderate Knee Osteoarthritis: A Rabbit Model - Li Y; Hou Y; Sun J; Wei J; Chai Y; Guo M; Wang R (Dove Medical Press, 2023)
Yuanyuan Li, Yimin Hou, Jiwei Sun, Jiabi Wei ,† Yemao Chai, Mengwei Guo, Rongguo Wang School of Acupuncture-Moxibustion and Tuina, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China†Jiabi Wei passed away on March 21, 2023Correspondence: Rongguo Wang, School of Acupuncture-Moxibustion and Tuina, Beijing University of Chinese Medicine, No. 11, Bei San Huan Dong Lu, Chaoyang District, Beijing, 100029, People's Republic of China, Tel +86 18518287139, Email wangguorongwgr3@126.comObjective: Acupotomy based on the meridian-sinew theory of traditional Chinese medicine has benefits in treating knee osteoarthritis (KOA). The current study aims to prove that acupotomy at the sinew points of Sanheyang protect the knee joint and alleviate the progression of moderate KOA by evaluating KOA symptoms, cartilage structure, and analyzing the changes of cytokines in rabbit cartilage.Methods: The model used was mono-iodoacetate-induced moderate KOA in the rabbit's right leg. Rabbits were divided into the model group, the acupotomy group, and the control group, with each group receiving two parts of treatment for 2 weeks and 4 weeks. We evaluated pain in the knee joint and range of motion. The articular cartilage sections were stained with Safranin O/Fast Green and Masson. We used immunohistochemistry and real-time PCR to detect the protein and mRNA expressions of collagen prototype II (COL-II), matrix metalloproteinase 13 (MMP13), and integrin-β 1 (ITG-β 1).Results: Compared with the model group, the acupotomy group had higher body weight, lower pain score, higher range of motion, lower Mankin score, and significantly lower protein and mRNA expression of MMP13. After 4 weeks of treatment, Col-II expression in the acupotomy group was significantly higher than that in the model group and the expression of ITG-β 1 in the model group was abnormally increased.Conclusion: Acupotomy at Sanheyang improved the pain symptoms and range of joint motion in rabbits with moderate KOA, and could protect Col-II by regulating MMP13, which may be related to ITG-β 1-mediated mechanical force transmission, thus reducing the damage to cartilage structure and delaying the progression of moderate KOA.Keywords: acupotomy, cartilage, gastrocnemius, knee osteoarthritis, sinew